2005
DOI: 10.4028/www.scientific.net/msf.490-491.503
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Residual Stresses in Micro Powder Injection Moulded Micro Bending Specimens Made of Zirconia

Abstract: Analysis of the residual stress state, the microstructure and surface topography of ceramic microcomponents made of Y2O3-stabilized ZrO2 produced by micro powder injection moulding were performed. During the production of the microspecimens sintering conditions were varied. The measurement of residual stresses has been carried out using the MAXIM (MAterials XRay IMaging) diffractometer at HASYLAB beamline G3 at DESY in Hamburg (Germany). The microstructure and surface topography of differently moulded specimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…In regard of earlier residual stress analyses (Kasanická et al 2005), the joining itself did not lead to higher stresses when compared to monolithic micro specimen. While those experiments did not investigate hydrostatic stresses, the deviatoric parts are similarly low compared to the tensile strength of the researched materials.…”
Section: Local Stress Distributionsmentioning
confidence: 97%
See 1 more Smart Citation
“…In regard of earlier residual stress analyses (Kasanická et al 2005), the joining itself did not lead to higher stresses when compared to monolithic micro specimen. While those experiments did not investigate hydrostatic stresses, the deviatoric parts are similarly low compared to the tensile strength of the researched materials.…”
Section: Local Stress Distributionsmentioning
confidence: 97%
“…This problem can be circumvented by averaging over certain areas on the specimen where constant stresses can safely be assumed. earlier works by (Kasanická et al 2005) using the Materials X-ray Imaging (MaXIm) (Wroblewski et al 1999) set-up at the G3 beamline at haSYlaB demonstrated the feasibility of the method on micro specimen. as it only gives access to stress components parallel to the specimen surface, this approach has not been considered for the investigations at hand.…”
Section: Introductionmentioning
confidence: 94%
“…Also, micro-hardness measurements were made on the polished cross sections of the sintered 316L micro-features using a micro-hardness tester with a Vickers indenter [29]. Residual stresses in zirconia specimens produced by μPIM were measured using a diffractometer [125]. Further studies on investigating mechanical properties of μPIM components can be found in the literature [126,127].…”
Section: Mechanical Propertiesmentioning
confidence: 99%
“…Using this technique and set up with the sin 2 Ψ method, laser beam weld in butt-joint configuration of two thin magnesium alloy (AZ31) sheets are investigated in this study. Such examinations using the setup described above were already done for other materials, steel [3,4] and zirconia [5].…”
Section: Introductionmentioning
confidence: 99%